A impossível ubiqüidade: uma representação melancólica da diáspora portuguesa: a ficção de Maria de Lourdes Hortas - Souza, Francisca Zuleide Duarte de (1999)
The topic of emigration goes through the Portuguese-Brazilian literature since its origin and comes to contemporarity by the multiple voices of the Portuguese writers scattered in the world. Maria de Lourdes Hortas, Portuguese-Brazilian poet and fiction writer, joins the tradition as she thematizes in her work the figure whitch is composed of a duplet of emigrant- exiled character who are victimized by "saudade" (homesickness) and the obsession for the return to homeland. Guided by Psychoanalysis, we investigate the representation of melancholy on the novels Adeus Aldeia (1 990) and Diário das Chuvas (1995), enfocalizing the psychic constitution of the characters Mariana (AA) and Tâmara (DC), revealed on the analysis through the repetition of symbols that configure the representation of Melancholy. The reading fososing in the poetic writing of the author, it was necessary articuiation to enter into other works of the author because of the studied texts.